2022
DOI: 10.3390/ijerph19137907
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Knowledge, Attitudes, and Practices of Lebanese Physicians Regarding Air Pollution

Abstract: Introduction: Air pollution imposes a significant burden on public health. It is emerging as a modifiable risk factor for cancer, diabetes, and respiratory and cardiovascular diseases. This study aims to assess the knowledge, attitudes, and practices of Lebanese physicians regarding air pollution. Methods: This observational study uses a descriptive cross-sectional correlational design. The data were collected using a self-administered online survey that was sent to 874 potential respondents who are members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…However, despite this awareness, four out of five medical students considered an ineffective measure, such as wearing face masks, helpful in reducing pollution’s harmful effects. This high level of knowledge aligns with other studies conducted in different populations, such as China, Ghana, Lebanon, the United States, Kuwait, Namibia, and Ireland, where a widespread acknowledgment of the hazards of air pollution was observed [ 29 , 32 , 33 , 34 , 38 , 39 , 40 , 41 ]. Regarding protective measures, studies have demonstrated that masks, especially N95 respirators, provide adequate protection approximately 74% of the time the respirator is worn, with a significant dependence on the type of respirator.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…However, despite this awareness, four out of five medical students considered an ineffective measure, such as wearing face masks, helpful in reducing pollution’s harmful effects. This high level of knowledge aligns with other studies conducted in different populations, such as China, Ghana, Lebanon, the United States, Kuwait, Namibia, and Ireland, where a widespread acknowledgment of the hazards of air pollution was observed [ 29 , 32 , 33 , 34 , 38 , 39 , 40 , 41 ]. Regarding protective measures, studies have demonstrated that masks, especially N95 respirators, provide adequate protection approximately 74% of the time the respirator is worn, with a significant dependence on the type of respirator.…”
Section: Discussionsupporting
confidence: 86%
“…There is a consensus that if society were better informed about the link between poor air quality and adverse health outcomes and were aware of actions that could mitigate pollution, individual, societal, and policy changes could be prompted [ 37 ]. Healthcare professionals play a crucial role in supporting these actions, starting with being well-informed about air pollution sources and then incorporating this knowledge into their practice and daily patient interactions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations